Disk spin-down measurements in the free-molecular flow regime: A new method for measurement of tangential momentum accommodation coefficients. (April 2016) - Acharya, Tathagata; Falgoust, Jordan; Rasmussen, Richard; Martin, Michael J.
Abstract: An experimental technique using spin-down of a disk approaching the free-molecular flow limit is developed to measure the tangential momentum accommodation coefficient σt . The new technique uses a disk mounted on a shaft supported by gas bearings in vacuum. A differential scavenging system allows disk spin-down experiments in different gases. Representative test results with two different materials in two different gases are shown, demonstrating the method is capable of handling a range of gases, as well as any material that is available as, or can be formed into, a planar disk. Highlights: We show a new technology for measuring momentum accommodation coefficients. We measure momentum accommodation at the free molecular flow limit. We successfully use a gas bearing stage in vacuum. The measured momentum accommodation values range between 0.7 and 1.